Ramipril + amlodipine and ramipril + hydrochlorothiazide fixed-dose combinations in relation to patient adherence. (October 2016) - Simonyi, Gábor; Ferenci, Tamás; Alföldi, Sándor; Farsang, Csaba
Objective: To compare 1-year treatment adherence of ramipril + amlodipine and ramipril +hydroclorothiazide fixed-dose combination therapies in patients with hypertension. Methods: Data were extracted from the database of the National Health Insurance Fund of Hungary. Treatment adherence was modelled using survival analysis. Results: At 2 months after initiation of treatment, 42% of patients using ramipril +hydrochlorothiazide ( n = 28, 800) had discontinued treatment, compared with 0% of patients using ramipril + amlodipine ( n = 10, 295). At 1 year, treatment adherence was 29% in the ramipril + hydrochlorothiazide group and 54% in the ramipril + amlodipine group. The hazard ratio for discontinuing ramipril + hydrochlorothiazide vs ramipril + amlodipine was 2.318 (95% confidence intervals 2.246, 2.392). Conclusion: Ramipril + amlodipine had significantly higher 1-year treatment adherence than ramipril + hydrochlorothiazide in patients with hypertension.